(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
This paper gives the explanations of the term “e-voting”. The term “e-voting” is used, in variety of different ways mainly and it encompasses all voting techniques involving electronic voting equipment, including voting over the internet, using booths in polling stations and sometimes even counting of paper ballots. Electronic voting (e-voting) is any voting method where the voter’s intention is expressed or collected by electronic means. There are considered the following electronic voting ways.